2011
DOI: 10.3758/s13421-010-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the anticipatory nature of pattern perception in sport

Abstract: The aim of the present study was to examine the anticipatory nature of pattern perception in sport by using static and moving basketball patterns across three different display types. Participants of differing skill levels were included in order to determine whether the effects would be moderated by the knowledge and experience of the observer in the same manner reported previously for simple images. The results from a pattern recognition task showed that both expert and recreational participants were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 33 publications
(50 reference statements)
11
71
4
3
Order By: Relevance
“…Gorman et al and Land et al have reported that experienced players predictively look ahead their lines of sight to the next destination [12,13]. In our experimental results, the experienced players predict the runners' movement and they moved their lines of sight to the first base.…”
Section: Discussionsupporting
confidence: 60%
“…Gorman et al and Land et al have reported that experienced players predictively look ahead their lines of sight to the next destination [12,13]. In our experimental results, the experienced players predict the runners' movement and they moved their lines of sight to the first base.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies concerning sports expertise effects on RM have reported that experts can perceive the next likely state of a play pattern, while novices cannot (Didierjean & Marmèche, 2005;Gorman et al, 2011). In addition to this qualitative difference, recent evidence from driving (Blättler et al, 2010(Blättler et al, , 2012 and basketball activities (Gorman et al, 2012) has shown that experts can perceive states further in the future than can novices (i.e., quantitative difference; see Gilis, Helsen, Catteeuw, & Wagemans, 2008 for an exception).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that when participants watched scenes of simulated road driving or aircraft landing scenes, experienced automobile drivers and aviation pilots had a larger forward displacement than did inexperienced individuals (Blättler, Ferrari, Didierjean, van Elslande, & Marmèche, 2010;Blättler, Ferrari, Didierjean, & Marmèche, 2011;Blättler, Ferrari, Didierjean, & Marmèche, 2012). In the sports domain, Gorman, Abernethy, and Farrow (2011) reported that when expert basketball players were provided with a static schematic or a moving video from their domain of expertise, the players perceived the next likely state of the play pattern (see also, Didierjean & Marmèche, 2005;Gorman, Abernethy, & Farrow, 2012). These studies indicate that knowledge acquired through years of experience with a particular behavioral domain (e.g., sports) modulates RM magnitude on perceptual judgments in the domain of expertise, and that experts in a particular domain have a more refined ability to extrapolate future events than do novices.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic visual stimuli were video clips of five-on-five basketball play (see Gorman et al 2011Gorman et al , 2012). The video footage was filmed using a stationary camera placed on a raised platform at the half-court position, with all players and all markings on one half of the court visible at all times.…”
Section: Apparatusmentioning
confidence: 99%